PENGARUH PENGAWASAN MANDOR TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PROSES PRODUKSI PADA PT. SURISENIA PLASMATARUNA KABUPATEN ROKAN HULU - Umi Kalsum; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to determine the effect of supervision on employee productivity foreman parts production process at PT. Surisenia Plasmataruna Rokan Hulu. Supervision as an independent variable (X) and produktiviitas work as the dependent variable (Y), and this study takes the number of respondents 49 people. Data was collected by questionnaire and interview techniques. Analysis of the data used is a simple linear regression analysis, with the help of SPSS.The results showed that there was a foreman supervision influence on employee productivity. From the analysis of data obtained value of t> t table is 3.777> 1.678 means that there is a significant effect between the foreman supervision on employee productivity. Value of determination R2 = 0.233 or 23.3 percent of this means that the variable foreman supervision has contributed in explaining the variable labor productivity by 23.3 percent. A percentage of 76.7 percent is contributed by other variables outside of this study.Keywords: Human Resource Management, Supervision, Work Productivity.